A monster calls Inspired by an idea from siobhan dowd. - Ness, Patrick (2011)
NOW A #1 NEW YORK TIMES BESTSELLER! An unflinching, darkly funny, and deeply moving story of a boy, his seriously ill mother, and an unexpected monstrous visitor, featuring stunning artwork by Jim Kay. At seven minutes past midnight, thirteen-year-old Conor wakes to find a monster outside his bedroom window. But it isn't the monster Conor's been expecting? he's been expecting the one from his nightmare, the nightmare he's had nearly every night since his mother started her treatments. The monster in his backyard is different. It's ancient. And wild. And it wants something from Conor. Something terrible and dangerous. It wants the truth. From the final idea of award-winning author Siobhan Dowd? whose premature death from cancer prevented her from writing it herself? Patrick Ness has spun a haunting and darkly funny novel of mischief, loss, and monsters both real and imagined.
Text Difficulty 3
MG+/Upper middle grades (6th-12th)
730
4.8
Electronic reproduction.
Keywords: Young Adult Fiction; Fantasy; Young Adult Literature; Electronic books